Case report: Short-term eculizumab use in atypical HUS associated with Lemierre's syndrome and post-infectious glomerulonephritis - Sadiq, Sanober; Urisman, Anatoly; Cil, Onur (Frontiers in Medicine, 2023)
Atypical hemolytic uremic syndrome (aHUS) is a rare disease caused by genetic abnormalities, infections, autoimmune diseases, drugs, and malignancies. Anti-C5 monoclonal antibody eculizumab is the mainstay of treatment of aHUS caused by the genetic defects of the alternative complement pathway. However, the utility of eculizumab in non-genetic forms of aHUS and the timing of treatment discontinuation remain controversial. Here, we report successful short-term eculizumab use in two young adult patients with aHUS due to rare infectious and autoimmune etiologies: Lemierre's syndrome and post-infectious glomerulonephritis, respectively. Eculizumab was rapidly discontinued in both patients with no aHUS recurrence during long-term follow-up. Considering its favorable safety profile with appropriate meningococcal prophylaxis, eculizumab can be considered as a treatment option for non-genetic aHUS.